The Impact of Digital Technology Implementation on the Productivity of MSMEs in Jakarta: An Analysis of E-commerce Adoption, Business Process Automation, and Business Growth - Loso Judijanto; Wawan Supriyanto; Ach. Afin; Eko Cahyo Mayndarto (Westscience Press, 2023)
This study explores the complex interrelationships between digital technology, e-commerce adoption, business process automation, and business growth in Micro, Small, and Medium-sized Enterprises (MSMEs) in Jakarta. Using Structural Equation Modeling, the study examines how these variables interact with a sample of businesses. The findings show strong positive correlations, suggesting that companies are more likely to use a whole range of digital technologies when they grow, automate processes, and implement e-commerce strategies. The results have practical ramifications for MSMEs in Jakarta, highlighting the strategic value of technology investment and proposing opportunities for automation and digitization to work together. E-commerce is becoming a more significant part of business operations, and this serves as a potent motivator for more extensive digital reforms. In addition to offering useful insights on the dynamics of digital adoption within the MSME sector, this research offers practical suggestions for companies and policymakers.